Arsenal Booking Inventory Management System for ROTU UiTM Shah Alam / Mohamad Nur Adib Mohd Nordin - Mohd Nordin, Mohamad Nur Adib (2017)
Arsenal Booking Inventory Management System (ABIMS) is the system that is developed to help cadet officer to book and borrow an arsenal as well as help instructor to manage the arsenal inventory in the arsenal storage of ROTU.UiTM Shah Alam Barrack. Arsenal storage of ROTU UiTM consists of (4) branches which is in UiTM Shah Alam, UiTM Lendu, UiTM Dungun and UiTM Arau. However, this project only cover for ROTU UiTM Shah Alam. The aim of this project is to manage the booking inventory of arsenal storage in ROTU Barrack in UiTM Shah Alam while the first objectives of this project is to gather and analyze the booking requirements and the requirements will be documented in Software Requirement Specification (SRS). Secondly, this project will make a design of the prototype system based on the requirements and the design prototype will be documented in Software Design Document(SDD). Lastly to develop the ABIMS for ROTU UiTM Shah Alam. Currently, the manual arsenal booking process in ROTU UiTM Shah Alam has many problems. The main problem that has been faced by the stakeholder is in charge cadet officer need to provide a log book in order for them to make a borrowing arsenal. This system may able to reduce the current problem of the arsenal booking in the arsenal storage of ROTU Barrack. Furthermore, this system also capable to assist instructor in order to manage the arsenal storage through ABIMS. Besides, the system would notify the booking status to cadet officer through email. In order for the booking request that need to get approval from the instructor, the system will execute function to send the booking request to the instructor’s page. Methodology that applied for this system is Waterfall Model. There are four (4) phases involved which are planning, analysis, design and last phase is implementation. All the necessary requirements for the system has been met. The programming language to build this system is based on Java language while oracle database is used to store system’s data. The future enhancement of this system is to provide an official website for ROTU UiTM enlarge the scope of the system with for all the (4) branches. As a conclusion, Arsenal Booking Inventory Management System (ABIMS) was developed to reduce the problem of the current arsenal booking process from manual booking to online booking.